Aplikasi Kalkulator Kalori Bagi Penderita Diabetes Mellitus Tipe 2 Menganut Panduan Perkeni 2011 - Ario Yusuf Christian; Nia Saurina; Firman Hadi S.P (Informatics Engineering Department-UWKS, 2016)
glucose levels under control. While many do not know how to adjust his diet because of lack of knowledge in calculating the energy needs for a diabetic patient. In this research is expected to make energy calculator application for people with diabetes mellitus manganut PERKENI guide 2011 which aims to calculate the nutritional needs of the people living with diabetes mellitus and sample the food. This study uses a Rapid Application Development (RAD), which includes Requirement Planning, collecting data needed sourced from literature studies Data collection of books and journals and interviews with nutritionists are competent in their field. This system design using UML (unified modeling language) with the creation of mobile-based applications. The level of patient satisfaction as a user is great in some aspects, namely the attractiveness, convenience, usefulness, timeliness, reliability applications. So the application can help patients to control diabetes mellitus without spending a lot of consulting